Epstein-Barr Virus Exploits the Secretory Pathway to Release Virions - Nanbo, Asuka (Microorganisms, 2020)
Herpesvirus egress mechanisms are strongly associated with intracellular compartment remodeling processes. Previously, we and other groups have described that intracellular compartments derived from the Golgi apparatus are the maturation sites of Epstein-Barr virus (EBV) virions. However, the mechanism by which these virions are released from the host cell to the extracellular milieu is poorly understood. Here, I adapted two independent induction systems of the EBV lytic cycle in vitro, in the context of Rab GTPase silencing, to characterize the EBV release pathway. Immunofluorescence staining revealed that p350/220, the major EBV glycoprotein, partially co-localized with three Rab GTPases: Rab8a, Rab10, and Rab11a. Furthermore, the knockdown of these Rab GTPases promoted the intracellular accumulation of viral structural proteins by inhibiting its distribution to the plasma membrane. Finally, the knockdown of the Rab8a, Rab10, and Rab11a proteins suppressed the release of EBV infectious virions. Taken together, these findings support the hypothesis that mature EBV virions are released from infected cells to the extracellular milieu via the secretory pathway, as well as providing new insights into the EBV life cycle.